2015
DOI: 10.1088/1674-4527/15/3/005
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of superhalo electrons generated by magnetic reconnection in the solar wind source region

Abstract: Superhalo electrons appear to be continuously present in the interplanetary medium, even at very quiet times, with a power-law spectrum at energies above ∼2 keV.Here we numerically investigate the generation of superhalo electrons by magnetic reconnection in the solar wind source region, using the MHD and test particle simulations for both single X-line reconnection and multiple X-line reconnection. We find that the direct current electric field, produced in the magnetic reconnection region, can accelerate ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(121 reference statements)
1
7
0
Order By: Relevance
“…Here we assume that S is similar to the total area of coronal holes that varies from 2.5% to 7.5% (5% in average) of the solar surface, measured by SOHO/EIT between 2006-2010 (Lowder et al, 2010). Thus, the number ratio η, varying from η 17% to η 50%, is consistent with the test particle simulations of electron acceleration in the solar wind source region by Yang et al (2015), but it is more than one order of magnitude larger than the number ratio (≈ 0.1% − 1%) estimated for solar HXR flares associated with solar energetic electron events (Lin, 1974;Pan et al, 1984;Krucker et al, 2007). Compared to solar flares that generally occur low in the corona, the superhalo sources likely lie high in the corona, leading to an easier escape of the accelerated electrons into the interplanetary space, i.e., a larger ratio of escaping electrons to downward-traveling electrons.…”
Section: Summary and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Here we assume that S is similar to the total area of coronal holes that varies from 2.5% to 7.5% (5% in average) of the solar surface, measured by SOHO/EIT between 2006-2010 (Lowder et al, 2010). Thus, the number ratio η, varying from η 17% to η 50%, is consistent with the test particle simulations of electron acceleration in the solar wind source region by Yang et al (2015), but it is more than one order of magnitude larger than the number ratio (≈ 0.1% − 1%) estimated for solar HXR flares associated with solar energetic electron events (Lin, 1974;Pan et al, 1984;Krucker et al, 2007). Compared to solar flares that generally occur low in the corona, the superhalo sources likely lie high in the corona, leading to an easier escape of the accelerated electrons into the interplanetary space, i.e., a larger ratio of escaping electrons to downward-traveling electrons.…”
Section: Summary and Discussionsupporting
confidence: 64%
“…Inspired by Yang et al (2015), we propose a scenario of small interchange reconnections (that are probably related to the solar wind source or coronal heating, e.g., nanoflares) to associate the superhalo electrons in the interplanetary space with the HXR emissions in the quiet Sun (see Figure 1). In this scenario, some of the accelerated electrons, e.g., by magnetic reconnection or turbulence, travel upwards along the open magnetic field lines into the interplanetary space, to form the solar wind superhalo population, while the rest propagate downwards into the lower atmosphere.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, energetic electron distributions in the Hermean magnetotail observed by MESSENGER often show power-law indices between 1.5 and 4 [15][16][17] . Turbulence contributes to the electron energization via the EMF − → ε M , in a similar way as a localized anomalous resistivity 55,56 . On the other hand, for weak turbulence (negligible or small EMF − → ε M , here Cases A and B), the rate of the change of the magnetic-field (∂B/∂t) dominates the electron energization, but the electrons just become heated and not significantly accelerated.…”
Section: Acceleration Sitesmentioning
confidence: 98%
“…Grady et al (2012) also showed that collapsing magnetic traps may lead to accelerating particles to high energies during solar flares. Meanwhile, features of particle acceleration have been investigated in different X-type magnetic field configurations (Browning & Vekstein 2001;Heerikhuisen et al 2002;Zharkova & Gordovskyy 2005;Hannah & Fletcher 2006;Petkaki & MacKinnon 2007;Liu et al 2009;Yang et al 2015;Xia & Zharkova 2018) as well. In addition, Dalla & Browing (2006, 2008 considered the fundamental properties of particle acceleration in a 3D current sheet including a spine and span and showed that in the spine reconnection particle escape takes place in two symmetric jets along the spine, in the fan reconnection no jet is produced, and particles escape in the fan plane.…”
Section: Introductionmentioning
confidence: 99%